Penerapan Kriptografi Enkripsi Dan Deskripsi Dalam Pendataan Pasien Klinik Mama Harfas Tembung Menggunakan Visual Basic - Rasyid Ridho; Cholil Bisri; Aninda Muliani Harahap (LPPM Universitas Dharma Andalas, 2023)
The security of patient data and drugs in the data collection process for the Mama Harfas Tembung Clinic is very important. In order to protect data, cryptographic algorithms are used, one of which is the Caesar cipher algorithm. The algorithm is applied to the patient and drug data collection systems with encryption and decryption methods. The encryption process is carried out before data creation, while decryption is applied when the system reads the encrypted data. In implementing the algorithm, it was shown that the data stored in the database was encrypted and could not be read easily by the main admin. In order to reduce the misuse of data and all the information in the system. The use of the cesarean chipper algorithm in the patient and drug data collection system for Mama Harfas Clinic is quite safe in maintaining clinical data.